2013
DOI: 10.1186/1476-9255-10-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel biomarkers for early prediction of sepsis-induced disseminated intravascular coagulation in a mouse cecal ligation and puncture model

Abstract: IntroductionThe objective of this study was to identify biomarkers of sepsis-induced disseminated intravascular coagulation (DIC) among platelet-derived factors using biotin label-based custom protein microarray technology in a mouse cecal ligation and puncture (CLP) model.MethodsKM mice were randomized into sham-operated and CLP groups. Blood samples were obtained immediately and at 1 h, 2 h, 6 h, 12 h, 24 h, 48 h and 72 h after establishment of the CLP for platelet count, coagulation assay and blood chemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
1
15
0
3
Order By: Relevance
“…The CLP model, by creating a bowel perforation with leakage of fecal material into the peritoneal cavity, is considered as closely resembling the course of sepsis observed in septic patients [22]. Our survival study demonstrated that the lethality of sepsis was markedly attenuated and delayed in septic mice administered with SDS probably due to the anti-inflammatory activity of SDS, which is consistent with the previous findings [23].…”
Section: Discussionsupporting
confidence: 87%
“…The CLP model, by creating a bowel perforation with leakage of fecal material into the peritoneal cavity, is considered as closely resembling the course of sepsis observed in septic patients [22]. Our survival study demonstrated that the lethality of sepsis was markedly attenuated and delayed in septic mice administered with SDS probably due to the anti-inflammatory activity of SDS, which is consistent with the previous findings [23].…”
Section: Discussionsupporting
confidence: 87%
“…However, we only observed a clotting profile consistent with hypocoagulability. The increases in plasma TF and PAI‐1 levels and the concurrent decrease in the plasma ATIII level and elevated D‐dimer level suggest an activated coagulation process with reduction in clot quality (i.e., decreased MCF) and consumption of platelets …”
Section: Discussionmentioning
confidence: 99%
“…*P < 0.05. Ctrl, control; PE, phycoerythrin quality (i.e., decreased MCF) and consumption of platelets 34.…”
mentioning
confidence: 99%
“…CD63 levels have recently been shown to be elevated in a mouse sepsisinduced DIC model. [27] A second possible biomarker related to the progression of the endothelial dysfunction is MFG-E8 (milk fat globule-EGF factor 8). It has been shown that, in septic mice, intestinal MFG-E8 expression is down-regulated leading to intestinal injury, impaired enterocyte migration and deficient mucosa regeneration.…”
Section: Discussionmentioning
confidence: 99%